Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.

Solve the equation 4e - 5 + 2e = e + 3 - 2e
for e.


Sagot :

Answer:e=8/7=1.143

Step-by-step explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

                    4*e-5+2*e-(e+3-2*e)=0

Add  8  to both sides of the equation :

                     7e = 8

Divide both sides of the equation by 7:

                    e = 8/7 = 1.143

And then you get

Divide both sides of the equation by 7:

                    e = 8/7 = 1.143

Answer:

                   4*e-5+2*e-(e+3-2*e)=0

Add  8  to both sides of the equation :

                    7e = 8

Divide both sides of the equation by 7:

                   e = 8/7 = 1.143

And then you get

Divide both sides of the equation by 7:

                   e = 8/7 = 1.143

Step-by-step explanation: